Factors Influencing Staff's Attitude Toward Electroconvulsive Therapy: A Comparison of New Versus Experienced Electroconvulsive Therapy Clinics. Issue 2 (June 2019) - Scholz-Hehn, Anne Deborah; Müller, Jana Christina; Deml, Ruben; Methfessel, Isabel; Zilles, David; Hädrich, Florian; Hecht, Gregory; Luedecke, Daniel; Gornisch, Janina; Albrecht, Heiko; Stumm, Laura; Freundlieb, Nils
Abstract : Objectives: Despite being a highly effective treatment, electroconvulsive therapy (ECT) is still stigmatized even among professionals. The aim of this study was to identify factors associated with a positive attitude toward ECT among health care workers. Methods: We investigated staff's attitude and their self-assessment of knowledge while introducing ECT in 3 German psychiatric clinics. Furthermore, we compared this data to that of a clinic where ECT has been applied with a long tradition. An anonymous questionnaire was answered by n = 182 employees in the ECT-introducing clinics ( novices ) and n = 68 employees in the clinic with a long history of ECT ( experts ). Results: Irrespective of the clinical history, the majority of participants approved the application of ECT in their clinic. Factors associated with a positive attitude were ( a ) profession (physicians presented a more positive mindset about ECT than nursing staff), ( b ) subjective feeling of being adequately informed, and ( c ) having had contact to patients undergoing ECT. Interestingly, the general attitude toward ECT did not differ between subjects who reported to have seen an ECT and those who had not. Conclusions: When introducing ECT as a new treatment into a clinic, formal information should be adapted to the needs of each profession with a special emphasis on nurses. To further increase acceptance, contact to ECT-experienced patients (professionals taught by patients) might result in a more positive attitude toward ECT than participation in an ECT treatment itself.